Critical Discourse Analysis of Lonely Song Lyrics by Justin Bieber - Evi Afipah; Zulfi Zumala Dwi Andriani (Darussalam English Journal, 2022)
Music is one of the means used by musicians to introduce a country's culture to the international community. In addition to the message they want to convey, their ideology and thoughts are also reflected in their songs. This study aims to determine the text analysis on Justin Bieber's song, entitled Lonely. Then, knowing the social cognition of the song Lonely created by Justin Bieber, as well as the social context in which the song developed. Text, social cognition, and social context were analyzed using Teun A. van Dijk's discourse analysis model. The research used in this study is a qualitative research type of library research. The research method used in this study is the intralingual and extralingual equivalent method. Based on the analysis that has been done, it can be concluded that the words used in the lonely song use simple words with a little figure of speech so that they are easy to understand. The social cognition of the song is based on the singer's mental awareness based on his personal experience and the social context in lonely song is a narrow view of the possible bouts of depression experienced by idols caused by society.